COMPARATIVE STUDY OF ADSORPTION ACTIVITY OF ACTIVATED CHARCOAL AND SILICA GEL IN CASE OF WATER/TOLUENE MIXTURES - Igor WINKLER (Stefan cel Mare University of Suceava, 2017)
Efficiency of the liquid phase adsorption of toluene has been investigated for two common and widely used adsorbents: activated charcoal and silica gel. The adsorption values were determined using the UV-photometry method, where the solution’s absorbance has been measured at the wavelength, which corresponds to the characteristic “benzene” peak of the adsorptive. It has been found that charcoal is a highly effective adsorbent for toluene, while silica gel reveals almost no adsorption activity towards this substance no matter if it is used raw or after desiccation. This conclusion can be used in the development of various adsorbents designed to decontaminate water or wastewaters from toluene and its homologues. Such adsorbents should be based mostly on activated charcoal as the most active substrate for the benzene-series hydrocarbons.